Situating Global Art topologies - temporalities - trajectories - Dornhof, Sarah; Hopfener, Birgit; Buurman, Nanne; Lutz, Barbara (Image, 2018)
Since the early 1990s, the term »Global Art« has gone hand in hand with an expansion of the canon while not always reflecting the plurality of art worlds. This volume interrogates the relations between an increasing globalization of artistic discourse and the situatedness of its practices. Focusing on multiple recent practices of art, curating, historiography and criticism, the contributions ask how contemporary forms of critique not only take into account new hegemonies and exclusions but also address transcultural entanglements in the arts. Thus, they challenge universalizing conceptions of art in the age of globalization.